Cat - Clutton-Brock, Juliet (New York : Distributed by Random House, 1991)
Text and photographs present the anatomy, behavior, habitats, and other aspects of wild and domestic cats.
"A Dorling Kindersley book"--T.p. verso.
Includes index.
Appraisal-Science Books for Young People.
Wilson's Children.
Wilson's Junior High School.
6.5
Keywords: Cats -- Juvenile literature; Felidae -- Juvenile literature; Cats; Felidae; Cats